First experience in the UK of treating women with recurrent urinary tract infections with the bacterial vaccine Uromune®. (23rd November 2017) - Yang, Bob; Foley, Stephen
Abstract : Objectives: To determine the effectiveness of Uromune ® in preventing recurrent urinary tract infections (UTIs) in women. Patients and Methods: A total of 77 women with microbiology‐proven recurrent UTIs were given Uromune sublingual vaccine for a period of 3 months. Time to first UTI recurrence since treatment and adverse events were prospectively recorded in a follow‐up period of up to 12 months. Results: Of the 77 women, 75 completed the treatment. Of the 75 women who completed treatment, 59 (78%) had no subsequent UTIs in the follow‐up period. Prior to treatment, all women had experienced a minimum of three or more episodes of UTI during the preceding 12 months. Proportionally, the majority of recurrences occurred in postmenopausal women. One patient had to stop treatment because of an adverse event (rash over face and neck). Conclusion: This prospective study suggests that Uromune is safe and effective at preventing UTIs in women. Further research is required in larger groups of patients for longer treatment times. An international double‐blind randomized control trial comparing Uromune with placebo is currently underway.